Article Pelatihan Pembuatan MPASI Tinggi Protein PROTIAS kepada Kader Posyandu di Wilayah Kerja Puskesmas Sukorambi Kabupaten Jember - Restuti, Arisanty; Yulianti, Adhiningsih; Ahmad, Arisona; Hartanto, Sugeng; Widyawatiningrum, Endang; Nurmasyitah, Vita; Ramadhany, Rendy Chairul (Universitas Muhammadiyah Surakarta, 2025)
Stunting prevention developing high-protein complementary foods (MP-ASI) and other nutrients needed by children for optimal growth and providing health education. PROTIAS is a high-protein MP-ASI based on Polije healthy rice flour combined with catfish meat flour. Community service activities are carried out by providing training to posyandu cadres on making PROTIAS MPASI made from rice flour combined with catfish meat flour as a healthy menu MPASI in the Puskemas Sukorambi working area, Jember. The activity was carried out in October 2024, located at the Dukuh Mencek Village Office, Sukorambi District, Jember. The training on making PROTIAS MP-ASI was carried out using a demonstration method related to how to make and process MP-ASI based on Polije healthy rice flour combined with catfish meat flour. The training activities were guided by lecturers, and involved technicians and students. Through this community service activity, it is expected to improve the knowledge and skills of posyandu cadres in assisting stunted toddlers. In addition, it is hoped that posyandu cadres can also utilize relatively cheap but highly nutritious local materials as MP ASI ingredients for stunted toddler.